2012
DOI: 10.1002/anie.201201244
|View full text |Cite
|
Sign up to set email alerts
|

A Bulky Biaryl Phosphine Ligand Allows for Palladium‐Catalyzed Amidation of Five‐Membered Heterocycles as Electrophiles

Abstract: Palladium-catalyzed amidation of five-membered heterocyclic bromides that contain multiple heteroatoms was achieved for the first time using the Pd/1 catalyst system. This system allows for efficient access to N-arylated imidazoles, pyrazoles, thiazoles, pyrroles, and thiophenes in moderate to excellent yield. Experimental results and DFT calculations point to the need for electron-rich and especially sterically demanding biaryl phosphine ligand to promote these difficult cross-coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 26 publications
4
92
1
Order By: Relevance
“…CD 2 Cl 2 , CDCl 3 , and toluene-d 8 were purchased from Cambridge Isotopes in sealed ampules and used without further purification. Preparations of AdBrettPhos ( 1 ) [7], t BuBrettPhos ( 6 ) [8], RockPhos ( 7 ) [8], 2 [1], 5 [9], 12 [10], 13 [9], 14 [10], and 17 [11] have been previously described. The t BuXPhos ( 8 ) used in this work was purchased from Sigma Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…CD 2 Cl 2 , CDCl 3 , and toluene-d 8 were purchased from Cambridge Isotopes in sealed ampules and used without further purification. Preparations of AdBrettPhos ( 1 ) [7], t BuBrettPhos ( 6 ) [8], RockPhos ( 7 ) [8], 2 [1], 5 [9], 12 [10], 13 [9], 14 [10], and 17 [11] have been previously described. The t BuXPhos ( 8 ) used in this work was purchased from Sigma Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…These ligands form well-defined bidentate mono-P-liganded Pd(0) species [45][46][47][48] with the structures formally corresponding to the 12-electron Pd-P(III) active catalysts of the SM reaction (Scheme 2, AC). The active catalyst is extremely reactive and readily undergoes oxidative addition reaction with aromatic halides to form intermediates with a welldefined structure I [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…In the case of C,P-complexes, 12-electron active catalyst is formed by dissociation of the Pd-C coordination bond (Scheme 2), and the energy of this process may influence the reaction rate. Several products of the oxidative addition possessing only one ligand at the phosphorus atom have been obtained and characterised [35,36,50,[60][61][62]. Thus, we decided to shed light on the energetic stability of the model chiral catalytic complex (Scheme 3).…”
Section: Catalyst Activationmentioning
confidence: 99%
“…[15a, 18] Using the productive results with Na-BHT,w ew ere able to develop arobust method for the amination of (hetero)aryl halides with primary aliphatic amines catalyzed by Pd-PEPPSI-IPent Cl complex 5.T he final conditions are shown at the top of Table 2. We found that av ariety of interesting aryl chloride electrophiles with functionality including methoxy (14), keto (15), cyano (16), carbomethoxy (17), 4-trifluoromethyl (18), o-methyl disubstituted (19), and 4-nitro (20)g roups could all be coupled in very high yield for the mono-aryl product, thus illustrating that the procedure is highly monoselective and broadly functional-group tolerant. In all instances where trace products were formed from overarylation, the desired mono-aryl product was readily isolated in pure form after column chromatography on silica gel.…”
mentioning
confidence: 92%
“…[19] However,w ef ound that simply Table 1: Influence of basic additives on the selectivity and conversion of 4-chloroanisole 6 and octylamine (7)i nto 8 in the presence of 5.…”
mentioning
confidence: 99%